Sengketa Merek Strong dan Penggunaan Kata Umum pada Merek Dagang (Studi Putusan Mahkamah Agung 332 K/ Pdt.Sus-Hki/2021) - Sihombing, Silvia; Aminah (Universitas Ekasakti, 2023)
Trademark becomes a valuable asset owned by a company, especially if the brand has become a well-known mark. The well-known of a trademark creates a greater opportunity for deviations in the use of the brand which will eventually lead to the trademark disputes. Trademark disputes are still common in Indonesia with various problems, especially imitation of famous trademarks. The purpose of this study was to determine the decision process of the judiciary regarding the